Utilizing Marhun Bih Based on Mutual Agreement According to Hanafi Fiqh and Syafi'i Fiqh (Case Study of Pegadaian Syariah Branch AR. Hakim Branch, Medan Area District, Medan City) - Muhammad Zulfahri Tambusai; Tetty Marlina Tarigan (Universitas KH. Abdul Chalim Mojokerto, 2025)
The utilization of Rahn collateral in the view of the Shafi'i madhhab and the Hanafi madhhab is very different whereas the Shafi'i madhhab tends to prohibit this implementation because it is feared that there is usury fadhli in its implementation. The Hanafi school of thought carries it out because it considers that this can be done as long as there is permission from the owner of the rahn collateral. This research uses empirical methods and a living case study approach, as well as a conceptual approach. This research took place at Pegadaian Syariah AR Hakim Branch. The results showed that in the provisions of the utilization of collateral, especially. The Shafi'i school of thought puts forward that the use and utilization of Rahn collateral cannot be carried out even with permission. However, according to the Hanafi school, it can be carried out if you get permission from the rahnun at the beginning of the contract. In its relevance in Pegadaian Syari'ah AR Hakim Branch in Medan City itself, the implementation of the utilization of Rahn collateral itself uses the principles of the Hanafi school of thought. Not only that, if you look at the relevance, of the implementation of the utilization of Rahn collateral itself in the community of Medan City, the Hanafi school is more relevant than the Shafi'i school even though the majority of adherents in Medan City are the Shafi'i school. This is due to the habit of the people of Medan City who consider the utilization of rahn collateral to be commonplace as long as no damage occurs.